Hematopoietic stem cell transplantation from HLA-matched sibling donors in children with acute lymphoblastic leukemia: A report from the Children’s Cancer Hospital Egypt - Hammad, Mahmoud; Hafez, Hanafy; Sidhom, Iman; Yassin, Dina; Salem, Sherine; Alsheshtawi, Khaled; Hamdy, Nayera; Elsharkawy, Nahla; Elhaddad, Alaa (Frontiers in Oncology, 2022)
Introduction Allogeneic hematopoietic stem cell transplantation (HSCT) is widely used for high-risk acute lymphoblastic leukemia (ALL) patients in their first complete remission (CR1), and for relapsed patients in second complete remission (CR2). Patients and methods We retrospectively analyzed data for 67 children with ALL, from a cancer center in a low/middle income country, who had undergone HSCT from human leukocyte antigen (HLA)-matched sibling donors (MSDs) using myeloablative conditioning (MAC) regimens, between 2007 and 2020, describing the survival outcome and relapse probability after achieving CR1 and CR2 and determining outcome differences in relation to indications for HSCT in patients transplanted in CR1. All patients had achieved a negative minimal residual disease prior to transplant (<0.01%). Results Forty-six patients (68.7%) were in CR1; 25 had adverse cytogenetics, including 18 patients with Philadelphia chromosome-positive ALL (Ph-positive ALL), and 21 had poor induction response. The 5-year overall survival (OS), event-free survival (EFS) and cumulative incidence of relapse (CIR) for the whole cohort were 56.1% (95% CI, 42.8%-69.4%), 49% (95% CI, 35.7%-62.3%) and 33.5% (95% CI, 21.7%-45.8%), respectively with better EFS and CIR for CR1 transplants compared to CR2 transplants (P=0.02 and P=0.03, respectively). Patients with Ph-positive ALL had better 5-year OS, EFS and non-relapse mortality (NRM) compared with other CR1 transplants (P=0.015, P=0.009 and P=0.028, respectively). Conclusion Hematopoietic stem cell transplantation from MSD for ALL in CR1 group had superior outcomes compared to CR2 group and was apparently a curable option for Ph-positive ALL without an increased risk of non-relapse mortality. Poorer survival rates and higher relapse probabilities were associated with HSCT conducted to patients who had a poor response to induction therapy or suffered a relapse.